Sustainability and health in portuguese canteens : an overview of the implementation of international and governmental guidelines - Martins, Catarina da Cunha Rodrigues Miranda (2022)
The growing societal urgency toward adopting more sustainable and healthier lifestyles and consumption motivates organizations to modify their practices and take on new ones. The food sector plays an extremely relevant role since food directly influences health, and food production causes significant pollution levels. Several guidelines are produced to mitigate these issues. Nonetheless, there is a gap in literature regarding which guidelines apply to the food industry and the process through which they are implemented within the sector. This thesis examines how Portuguese canteens implement sustainable and healthier guidelines produced by the Government and international organizations. To answer the research question, I conducted a multiple case study on two canteens and two collective catering companies. The phenomenon of how canteens translate sustainable and healthier guidelines in the implementation process was studied in light of the Scandinavian institutionalism theoretical framework. Results show that Portuguese canteens have been placing great effort into promoting sustainability and health. However, they tend to focus more on Portuguese guidelines rather than international ones. Interestingly, Portuguese guidelines are inspired by international ones.